2016
DOI: 10.1002/chem.201602844
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐Catalyzed ortho‐Arylation of Aromatic Alcohols with a Readily Attachable and Cleavable Molecular Scaffold

Abstract: A palladium(II)-catalyzed C–H arylation process of alcohols has been developed. The strategy utilizes a novel quinoline-based hemiacetal scaffold that can direct the selective C–H bond functionalization. This reaction provides a useful method to construct biaryl compounds of benzyl alcohols in good to excellent yields. The new molecular scaffold can be readily attached, removed, and recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Moreover, the synthetic potential of this PyA auxiliary was further highlighted by the fact that it could be installed in a one-pot process, followed by C−H alkenylation, and could then be removed to afford the corresponding alkenylated arene alcohol 309 in good yield with the directing group being recovered in high yield (Scheme 144b). Using a similar N,O-based directing group that contains a quinoline-based acetal (QuA), Ferreira subsequently reported the Pd-catalyzed ortho-arylation of the benzyl alcohol derivative 310 with arylboron reagents (Scheme 145a) 578 and the meta-arylation of the benzyl alcohol derivative 312 with aryl iodides in combination with a Pd/ norbornene-CO 2 Me catalytic system (Scheme 145b). 579 In 2017, Lupton and Maiti reported the Pd-catalyzed metaselective C(sp 2 )−H bond alkenylation with activated alkenes aided by an 8-nitroquinoline-or 8-methoxyquinoline-based directing groups (Scheme 146).…”
Section: Arylation and Alkynylation Continuous Efforts Bymentioning
confidence: 99%
“…Moreover, the synthetic potential of this PyA auxiliary was further highlighted by the fact that it could be installed in a one-pot process, followed by C−H alkenylation, and could then be removed to afford the corresponding alkenylated arene alcohol 309 in good yield with the directing group being recovered in high yield (Scheme 144b). Using a similar N,O-based directing group that contains a quinoline-based acetal (QuA), Ferreira subsequently reported the Pd-catalyzed ortho-arylation of the benzyl alcohol derivative 310 with arylboron reagents (Scheme 145a) 578 and the meta-arylation of the benzyl alcohol derivative 312 with aryl iodides in combination with a Pd/ norbornene-CO 2 Me catalytic system (Scheme 145b). 579 In 2017, Lupton and Maiti reported the Pd-catalyzed metaselective C(sp 2 )−H bond alkenylation with activated alkenes aided by an 8-nitroquinoline-or 8-methoxyquinoline-based directing groups (Scheme 146).…”
Section: Arylation and Alkynylation Continuous Efforts Bymentioning
confidence: 99%
“…98 Here, a cocktail of acetates containing LiOAc$2H 2 O, CsOAc, as well as Cu(OAc) 2 $H 2 O, and AsPh 3 as the optimal ligand were found to be crucial to obtain satisfactory product yields. The powerful palladium(II)/norbornene-catalyzed meta-selective C-H activation process could be further extended to benzylsulfonamides 99 and benzylic alcohols 100 by Yu and co-workers and Ferreira and coworkers, respectively.…”
Section: C-h Functionalization With Norbornene Mediatormentioning
confidence: 99%
“…A sequential procedure of arylation with immediate subsequent scaffold cleavage afforded biaryl alcohol 6 an in 83 % yield . Methyl acetal‐derived scaffold (QuAOMe, 7 ) was also recovered in 94 % yield; we have shown that this compound can be reused in further attachment sequences . Furthermore, a telescoping procedure for this meta ‐arylation process using our quinolinyl scaffold could also be performed.…”
Section: Figurementioning
confidence: 96%